IMPROVING ENGLISH SPEAKING SKILLS IN DAILY CONVERSION FOR YOUTH IN THE TEMPE DISTRICT - Satriani Satriani; Muhammad Hasbi (Perkumpulan Dosen Muslim Indonesia, 2021)
The Wajo Regency administration is currently concerned about the development of tourism attractions; tourist attractions are being refurbished and renovated in order to attract tourists from within and beyond the Regency, as well as the local government expecting tourists. tourism enhancement program must be complemented by an increase in human resources, particularly in the field of English, because regional advancement continues to increase, as evidenced by improvements in the city of Sengkang in terms of better structuring specific tourist sites. Human resource development can take the form of English classes in addition to building a responsible workforce and developing regional potential (becoming a tourist guide), as well as encouraging adolescents to participate actively in government tourism programs.